Social Reactions toward Online Disclosure of Sexual Violence - Azijah, Sarah Marchiani Nur; Asriani, Desintha Dwi (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2023)
Many survivors of sexual violence have come forward to disclose their experiences on social media. The disclosure has generated positive and negative social reactions. Social media users either victimize sexual violence survivors or advocate against it, according to previous studies. This study aims to explore Twitter users’ social reactions to sexual violence disclosure and their narratives. This study used social network analysis and analyzed 1,678 tweets extracted from the Twitter search function. This study discovers two major themes and twelve subthemes of social reactions. New subthemes emerged: condemnation, curiosity, and sharing experiences (positive social reactions) and humor (negative social reactions). The narratives within negative social reactions brought digital harm to sexual violence survivors with prejudice, hostility, and normalization of sexual violence. Meanwhile, positive social reactions represent resistance by challenging harmful users and the authority and retelling sexual violence experiences to a bigger audience. This study provides input to design policy interventions to guide social media users in responding to sexual violence disclosures.